Lipoprotein lipase expression exclusively in liver. A mouse model for metabolism in the neonatal period and during cachexia. - Merkel, M (1998)
Lipoprotein lipase (LPL), the rate-limiting enzyme in triglyceride hydrolysis, is normally not expressed in the liver of adult humans and animals. However, liver LPL is found in the perinatal period, and in adults it can be induced by cytokines. To study the metabolic consequences of liver LPL expression, transgenic mice producing human LPL specifically in the liver were generated and crossed onto the LPL knockout (LPL0) background. LPL expression exclusively in liver rescued LPL0 mice from neonatal death. The mice developed a severe cachexia during high fat suckling, but caught up in weight after switching to a chow diet. At 18 h of age, compared with LPL0 mice, liver-only LPL-expressing mice had equally elevated triglycerides (10,700 vs. 14,800 mg/dl, P = NS), increased plasma ketones (4.3 vs. 1.7 mg/dl, P < 0.05) and glucose (28 vs. 15 mg/dl, P < 0.05), and excessive amounts of intracellular liver lipid droplets. Adult mice expressing LPL exclusively in liver had slower VLDL turnover than wild-type mice, but greater VLDL mass clearance, increased VLDL triglyceride production, and three- to fourfold more plasma ketones. In summary, it appears that liver LPL shunts circulating triglycerides to the liver, which results in a futile cycle of enhanced VLDL production and increased ketone production, and subsequently spares glucose. This may be important to sustain brain and muscle function at times of metabolic stress with limited glucose availability.